SUSTAINABLE MANAGEMENT OF MRINE TOURISM: SOME ECONOMIC CONSIDERATIONS *) - Derrin Davis (JOURNAL OF COASTAL DEVELOPMENT, 1998)
Marine tourism is a rapidly growing phenomenon world-wide. Concerns arise that important marine resources, such as coral reefs, are used sustainably for recreation and other pursuits. A number of possible management strategies exist that might contribute to such result should considers the followings: property-rights;user-pays;regulation;education and code of conduct;permanent mooring;socio-economic research. It is also clear that no one management strategy will ensure that Indonesia’s significant coral reef and other marine are conserved and used in sustainable fashion. Rather, a judicious blend of the use of economic instruments and concepts, regulation, education, and “site-hardening” (e.g. by use mooring) is required to ensure that marine tourism is sustainable.